Outcome of superficial squamous cell carcinoma of the esophagus: a clinicopathological study - Henry, Maria Aparecida Coelho de Arruda [UNESP]; Lerco, Mauro Masson [UNESP]; Naresse, Luiz Eduardo [UNESP]; Crema, Eduardo; Rodrigues, Maria Aparecida Marchesan [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To analyze the clinicopathological features and outcome of patients with pathologically proven superficial squamous cell carcinoma of the esophagus. METHODS: A total of 234 consecutive cases of esophageal carcinoma in a 15-year period were reviewed. RESULTS: Superficial esophageal cancer was found in five patients (2.1%). They were four men and one woman and the mean age was 52.5 years. Smoking and alcohol were the main risk factors. Achalasia due to Chagas disease occurred in one patient and a second primary tumor developed in the larynx in another patient. Four patients underwent esophagectomy and one patient received chemoradiotherapy. The histopathologic diagnosis was of squamous cell carcinoma in all cases. Intramucosal tumor (Tis) was identified in three cases and superficially invasive carcinoma in two cases. Four patients are free of disease with survival times of two, four, six and nine years. The patient who developed laryngeal cancer died six years after esophagectomy. CONCLUSION: Long-term survival in patients with esophageal cancer is related to early diagnosis. Therefore, a less aggressive surgical approach, such as endoscopic resection, may be a good option for these patients, if depth of tumor invasion can be accurately predicted by the new imaging tools.
Keywords: Carcinoma; Squamous Cell; Esophageal Neoplasms; Early Detection of Cancer